2012
DOI: 10.3892/ol.2012.625
|View full text |Cite
|
Sign up to set email alerts
|

The clinical usefulness of urinary N1,N12-diacetylspermine (DiAcSpm) levels as a tumor marker in patients with colorectal cancer

Abstract: Abstract. The aim of this study was to evaluate the usefulness of urinary N 1 ,N 12 -diacetylspermine (DiAcSpm) measured by the colloidal gold aggregation method as a tumor marker for colorectal cancer (CRC). The preoperative urine of 113 CRC patients was collected, and the urinary DiAcSpm was measured by a reagent kit for DiAcSpm determination based on colloidal gold aggregation using automatic biochemical analyzers. The urinary DiAcSpm levels significantly correlated with distant metastasis and Tumor-Node-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Rapidly growing cells, such as cancer cells, generally have increased intracellular polyamine levels and actively metabolize polyamines. An elevated N 1 , N 12 -diacetylspermine level may indicate rapid proliferation of cancer cells themselves 32 , and has been reported as a more sensitive biomarker than CEA, CA19-9 or CA15-3 for CRC diagnosis at early stages 30 , 31 , 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Rapidly growing cells, such as cancer cells, generally have increased intracellular polyamine levels and actively metabolize polyamines. An elevated N 1 , N 12 -diacetylspermine level may indicate rapid proliferation of cancer cells themselves 32 , and has been reported as a more sensitive biomarker than CEA, CA19-9 or CA15-3 for CRC diagnosis at early stages 30 , 31 , 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…CRC is one of the leading causes of cancer deaths in the world, and diagnosis at an early onset followed by surgical intervention is currently the best way to cure the disease and decrease mortality. It is therefore important to develop detection markers to detect asymptomatic CRCs at earlier stages, while the sensitivities of CEA and CA19‐9 were reported to be relatively low in early‐stage CRCs . Our previous studies of DNA methylation in CRC and precancerous lesions revealed that accumulation of aberrant DNA methylation was mostly completed by the adenoma stage , suggesting the possible usefulness of assessing aberrant methylation in plasma DNA in detecting early‐stage CRCs.…”
Section: Discussionmentioning
confidence: 99%
“…The fecal occult blood test, however, has a low specificity, ranging from 0.3% to 0.5% . CEA and CA19‐9 are not frequently positive in CRC at early stages (I and II), and their sensitivities are <50% . These methods are not satisfactory for early cancer detection, and a new, noninvasive technique to detect early‐stage malignancies with higher sensitivity than these protein markers would be useful as a first screening test, before the need of invasive examinations, for example, barium enemas and colonoscopies .…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of acetylated polyamines (APs) in urine have long been associated with cancer [1]. Specifically, N 1 ,N 12 -diacetylspermine (DAS), N 1 -acetylspermine (ASP), and N 8acetylspermidine (ASD) have been found to be elevated in urine of patients with a wide range of cancer types [2][3][4][5][6][7][8]. In recent years APs have been found to be elevated in matrices other than urine [9].…”
Section: Introductionmentioning
confidence: 99%